CERTAIN OBSERVATIONS ON THE DOUBLE COCOONS OF SOME PURE AND HYBRID COMBINATIONS OF BOMBYX MORI LINN. - YADAV, P.R.; ., CHANDRASHEKHARAIAH; SAMSON, M.V. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1994)
Observations on the double cocoons in relation to sex association and orientation pattern of pupae of nine pure and hybrid combinations have been made. Double cocoon formation percentage was in between 1.79 to 6.38. Male female sex association was found more in both the pure and hybrids excepting a multivoltine race (pnd-rech) where it was only 28.57%. Orientation pattern of pupae in the same direction was in the range of 92-95%. Overall sex ratio of male and female was almost 1: 1 excepting two pure races i.e. pnd-rech (MV) and NB18 (BV) where it was in the ratio of 1: 1.8 and 1: 1.5, respectively.